2008
DOI: 10.1074/jbc.m802751200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Increases the Cdt1-to-Geminin Ratio Inducing DNA Re-replication and Polyploidy

Abstract: Hepatitis B virus X protein (pX) is implicated in hepatocellular carcinoma pathogenesis by an unknown mechanism. Employing the tetracycline-regulated pX-expressing 4pX-1 cell line, derived from the murine AML12 hepatocyte cell line, we demonstrate that pX induces partial polyploidy (>4N DNA). Depletion of p53 in 4pX-1 cells increases by 5-fold the polyploid cells in response to pX expression, indicating that p53 antagonizes pX-induced polyploidy. Dual-parameter flow cytometric analyses show pX-dependent bromod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 69 publications
3
62
0
1
Order By: Relevance
“…This surplus CDC6 can participate in licensing of origins in quiescence and early G 1 phase, which may induce untimely initiation of DNA replication. In agreement with this observation, it has been reported that HBx-expressing murine AML12 hepatocytes overexpress CDC6 and Cdt1 origin licensing factors and exhibit polyploidy (29).…”
Section: Cdc6 and Apcsupporting
confidence: 80%
See 1 more Smart Citation
“…This surplus CDC6 can participate in licensing of origins in quiescence and early G 1 phase, which may induce untimely initiation of DNA replication. In agreement with this observation, it has been reported that HBx-expressing murine AML12 hepatocytes overexpress CDC6 and Cdt1 origin licensing factors and exhibit polyploidy (29).…”
Section: Cdc6 and Apcsupporting
confidence: 80%
“…Despite ever increasing data proving that HBx adversely affects cell cycle regulatory proteins and causes DNA replication defects, there is no direct evidence linking viral HBx with DNA replication. Further, the regulation of DNA replication proteins such as CDC6 and Cdt1 by HBx is also poorly understood (29).…”
Section: Cdc6mentioning
confidence: 99%
“…In optimal growth factor conditions, pX-expressing cells do not undergo apoptosis but instead exhibit accelerated and unscheduled S phase entry, activation of the DNA damage checkpoint, and eventual progression to mitosis (49). Interestingly, in optimal growth conditions, pX expression promotes DNA re-replication-induced DNA damage by enhancing expression of replication initiation factors Cdt1 and Cdc6, while inhibiting expression of geminin, the negative regulator of re-replication (52). Intriguingly, despite DNA re-replicationinduced DNA damage, these pX-expressing hepatocytes proceed through mitosis, propagate damaged DNA, and generate daughter cells that are partially polyploid (Ͼ4N DNA) (52).…”
mentioning
confidence: 99%
“…Interestingly, in optimal growth conditions, pX expression promotes DNA re-replication-induced DNA damage by enhancing expression of replication initiation factors Cdt1 and Cdc6, while inhibiting expression of geminin, the negative regulator of re-replication (52). Intriguingly, despite DNA re-replicationinduced DNA damage, these pX-expressing hepatocytes proceed through mitosis, propagate damaged DNA, and generate daughter cells that are partially polyploid (Ͼ4N DNA) (52). Partial polyploidy induced by pX results in oncogenic transformation (40).…”
mentioning
confidence: 99%
“…Perturbation of the balance between Cdt1 and geminin by HBX may be a direct cause of DNA rereplication in this case. Although the authors did not address how HBX deregulates the licensing factors, the significantly altered mRNA levels of Cdt1, Cdc6 and geminin suggest that HBX may exert its effect by regulating transcription of these genes (Rakotomalala et al, 2008). Alternatively, the fact that HBX is able to interact with Ddb1, a common linker protein in the CUL4 ubiquitin complex, and disrupt CRL4…”
Section: Viral Infection Disrupts Dna Replication Licensing In the Homentioning
confidence: 99%